Abraham Lincoln - D'Aulaire, Ingri, 1904-1980.; D'Aulaire, Edgar Parin, 1898-1986. (New York Dell Publishing, 1993)
Lincoln as child and adult is shown with humor and insight.
"A Picture yearling special."
Reprint. Originally published: 1939.
900
Accelerated Reader AR
Keywords: Lincoln, Abraham, -- 1809-1865 -- Biography; Presidents -- United States -- Biography